Effects of Ciprofol and Propofol General Anesthesia on Postoperative Recovery Quality in Patients Undergoing Ureteroscopy: A Randomized, Controlled, Double-Blind Clinical Trial - Shi S; Wu J; Wu Y; Han X; Dai H; Chen X; Sun Z; Wang F (Drug Design, Development and Therapy)
Shuqi Shi,1,2,* Jimin Wu,1,* Yini Wu,1 Xin Han,1 Hong Dai,1 Xuedong Chen,3 Zhangnan Sun,4 Faxing Wang1,2 1Department of Anesthesiology, Lishui People’s Hospital, Wenzhou Medical University Lishui Hospital, The First Affiliated Hospital of Lishui University, Lishui, People’s Republic of China; 2Oujiang Laboratory (Zhejiang Lab for Regenerative Medicine, Vision and Brain Health), Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 3Department of Urology, Lishui People’s Hospital, Wenzhou Medical University Lishui Hospital, The First Affiliated Hospital of Lishui University, Lishui, People’s Republic of China; 4Department of Anesthesiology, The Second Hospital of Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Faxing Wang, Department of Anesthesiology, Lishui People’s Hospital, Wenzhou Medical University Lishui Hospital, The First Affiliated Hospital of Lishui University, No. 15, Dazhong Street, Lishui, Zhejiang Province, 323000, People’s Republic of China, Email wfx2023@wmu.edu.cn Zhangnan Sun, Department of Anesthesiology, The Second Hospital of Hebei Medical University, Shijiazhuang, Hebei, 050000, People’s Republic of China, Email 28703077@hebmu.edu.cnObjective: This study compares postoperative recovery quality between Ciprofol and Propofol, providing a reference for the clinical application of anesthetics.Methods: We randomized 112 patients undergoing ureteroscopic surgery into two groups: the Ciprofol group (Group C), with an induction dose of 0.4 mg/kg and a maintenance dose of 0.8– 1.5 mg/(kg·h), and the Propofol group (Group P), with an induction dose of 2 mg/kg and a maintenance dose of 4– 10 mg/(kg·h). Both groups received sevoflurane at a concentration of 1%. The Bispectral Index (BIS) was maintained between 40 and 60. The primary outcomes were the Quality of Recovery-15 (QoR-15) scores on postoperative day 1 (POD1). Secondary outcomes included hemodynamic parameters, vasopressor use, timing indicators, sedative consumption, BIS values, Riker Sedation-Agitation Scale (R-SAS) scores, urinary tract symptoms, patient satisfaction, and adverse events.Results: No significant differences were observed in QoR-15 scores between the two groups. Although Group C had higher pain (P = 0.004) and comfort (P = 0.002) scores on POD1, these differences were not clinically significant. The incidence of hypotension and vasopressor use was lower in Group C, which had more stable hemodynamics. Additionally, the time from induction to BIS ≤ 60 was shorter in Group P (P = 0.001), while Group C had lower BIS values from drug discontinuation to full recovery of consciousness (P = 0.001). The incidence of urinary tract symptoms on POD1 was lower in Group C (P = 0.043). There were no significant differences in time to spontaneous breathing recovery, extubation, recovery room stay, time to first ambulation, hospital stay, patient satisfaction, or other adverse events.Conclusion: Ciprofol provides comparable early postoperative recovery to Propofol during ureteroscopy and may be a preferable alternative for urological procedures, especially in patients with blood pressure concerns.Trial Registration: Chinese Clinical Trial Registry (ChiCTR2400082736).Keywords: ciprofol, propofol, postoperative recovery quality, ureteroscopic surgery